Studies on Differential Shrinkage in Different Planes of Wood - DasGupta, P. R. (Indian Forester, 1980)
This paper deals with the statistical analysis on different shrinkage characteristics of Gurjan, Badam and white Chuglam, the three important species of Andaman Forests. The quotient for tangential/radial shrinkages on aide specimens (T/R) and on cross face specimens (t/r) of the above three species at different moisture content are tabulated. Galton’s graphs drawn with them indicate the unequal ratios in the two series. Gurjan and Badam have highly significant perfect positive co-efficient or correlation in their T/R and t/r series. Whereas white Chugalam has highly signincant perfect negative co-efficient of correlation. Such negative correlation in white Chuglam may be due to abnormal steepness of its tangential (T) shrinkage curve. The probable effect or this on the character or white Chuglam is discussed in the paper.